Pengurapan dalam Kitab-Kitab Taurat Membawa Perkenanan Allah - Subekti, Tri; Immanuela Deru; Indriati Tjipto Purnomo; Ipan Morris Pangaribuan; Mulianto Mulianto (REDOMINATE Jurnal Teologi dan Pendidikan Kristiani, 2024)
The law states that the essence of human being is creation of God the Creator of the universe. God is Spirit. The time God created man, Adam, He formed it from the dust of the earth. When God breathed his Spirit then that man was alive physically, phsycologically and spiritually. Worshipping God is a logical consequence for man for its creation. The purpose of anointing is that the worshippers adapted to the nature of God, the Most Holy One. By this they are made holy before God. The reason is that man had fallen into sin. That sin separated him from the presence of the Most Holy God. A curse from God and difficulty in live make man realize if he needs God. The matter is that man in his own effort of his idea can not please God and come to him. Sin has separated man from the holy God. The research uses a qualitative methode, by mean of describing and acquiring the understanding values and the quality of the Law’s anointing.